2008
DOI: 10.1016/j.ijgo.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner and nonpartner violence against pregnant women in rural Haiti

Abstract: Objective To examine the association between violence experienced by pregnant Haitian women in the previous 6 months and pregnancy-related symptom distress. Methods A total of 200 women seeking prenatal care at community health dispensaries in the Artibonite Valley were interviewed. Results Over 4 in 10 women (44.0%) reported that they had experienced violence in the 6 months prior to interview; 77.8% of these women reported that the violence was perpetrated by an intimate partner. Those who experienced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…For instance, in practice, rape within marriage is not prosecuted within the Haitian court system despite legal advances over the past 20 years which have clearly defined rape to include forced sexed which occurs in an existing romantic relationship. Traditional gender roles in Haitian culture subjugate a woman's desires to that of her male partners leaving reluctant women with the perception that they are forced or obligated to have sex even when they desire to refrain (Faedi 2008;Joshi et al 2014;Lankenau 2012;Rahill et al 2015;Small et al 2008).…”
Section: Sexual and Romantic Relationships In Haitian Culturementioning
confidence: 99%
“…For instance, in practice, rape within marriage is not prosecuted within the Haitian court system despite legal advances over the past 20 years which have clearly defined rape to include forced sexed which occurs in an existing romantic relationship. Traditional gender roles in Haitian culture subjugate a woman's desires to that of her male partners leaving reluctant women with the perception that they are forced or obligated to have sex even when they desire to refrain (Faedi 2008;Joshi et al 2014;Lankenau 2012;Rahill et al 2015;Small et al 2008).…”
Section: Sexual and Romantic Relationships In Haitian Culturementioning
confidence: 99%
“…In African countries, the overall prevalence rates of IPV during pregnancy are some of the highest in the world, as high as 25, 34 and 61% in Ethiopia, Zimbabwe and the Gambia respectively 3 6 8 14. It has been suggested that IPV against women and its effects may be exacerbated in resource-limited settings, such as Rwanda and many other African countries, due to gender inequality and cultural and economic barriers that restrain women in becoming economically independent 15 16. This situation compels women to accept violence exposure from the husband/partner, and the healthcare services are most often inadequate in terms of identifying abused women and offering support.…”
Section: Introductionmentioning
confidence: 99%
“…IPV during pregnancy has been associated with a variety of obstetrical risks, including late prenatal care, self-care deficits, abusive use of tobacco, alcohol and other substances, suicide attempts, depression, posttraumatic stress syndrome, sexually transmitted infections, unwanted pregnancies, pregnancy during adolescence, vulvovaginitis, bleeding, miscarriage, urinary tract infections, in addition to deficits in weight gain during pregnancy and violent deaths during pregnancy [2][3][4][5][6][7][8] . More severe consequences during pregnancy are described, including placenta previa, uterine rupture, hypertensive disorders, and chorioamnionitis, among others [9][10][11][12][13] .…”
mentioning
confidence: 99%